Active Learning Strategies In Arabic Language Teaching Between Theory And Practice In Public Education Institutions In The United Arab Emirates : A Descriptive Study - Yuslina Mohamed; Ahmad Abdurrahman Al Kasem; Nada Ibrahim Alribdi (Ijaz Arabi Journal of Arabic Learning, 2026)
Public education institutions in the United Arab Emirates are characterized by their continuous commitment to improving the quality of education and advancing the educational process in alignment with the demands of the modern era. In this context, the importance of conducting an analytical and descriptive study on the application of active learning in these institutions becomes evident. The aim is to understand the effectiveness of these strategies in achieving educational goals, developing students' skills, and engaging them in the learning process. This study aims to explore and analyze the implementation of active learning strategies in teaching Arabic language in public schools in the United Arab Emirates (UAE). This qualitative study employed a descriptive–analytical approach to examine the implementation of active learning in educational institutions, with the aim of evaluating its effectiveness in achieving instructional objectives, enhancing students’ skills, and fostering meaningful engagement in the learning process. The study further explored the application of active learning within public educational institutions in the United Arab Emirates by analyzing the educational context and prevailing instructional practices. The findings indicate a sustained effort to promote a culture of active learning, systematic evaluation of active learning strategies by the Ministry of Education, and ongoing encouragement for teachers to adopt these strategies in their classrooms.